Life in Limbo: why do Rohingya refugees remains reside in Malaysia? - Atika Shafinaz Nazri,; Aireen Grace Andal,; Andika Ab Wahab, (Penerbit Universiti Kebangsaan Malaysia, 2024)
We do not deny that residing in Malaysia presents formidable challenges, particularly for Rohingya refugees, due to the increasingly prevalent xenophobic attitudes towards them. Consequently, the question arises: "Despite the numerous hardships they must face, why do they remain to reside in Malaysia?" The theoretical aim of our study is to elucidate that despite the challenges, refugees still have the capacity to lead meaningful lives. Based on interviews with seven Rohingya refugees, our findings suggest that factors including the peaceful region, family members and friends, acts of kindness and generosity, and support from organizations, especially the United Nations High Commissioner for Refugees (UNHCR) and non-governmental organizations (NGOs), motivate refugees to remain in Malaysia. These indicators stem from Malaysia's status as a peaceful region, which facilitates the emergence of these factors in refugees' lives. In summary, refugee life is not as dire as previously portrayed in much of the literature; they still possess what we refer to as "spaces," as this group is capable of leading lives that include informal employment, education, and receiving aid and support, whether from state or non-state actors. These spaces serve as a crucial function in justifying why Rohingya refugees choose to remain in Malaysia.